Shifts in methanogenic community composition and methane fluxes along the degradation of discontinuous permafrost - Liebner, Susanne; Ganzert, Lars; Kiss, Andrea; Yang, Sizhong; Wagner, Dirk; Svenning, Mette M. (Frontiers in Microbiology, 2015)
The response of methanogens to thawing permafrost is an important factor for the global greenhouse gas budget. We tracked methanogenic community structure, activity, and abundance along the degradation of sub-Arctic palsa peatland permafrost. We observed the development of pronounced methane production, release, and abundance of functional (mcrA) methanogenic gene numbers following the transitions from permafrost (palsa) to thaw pond structures. This was associated with the establishment of a methanogenic community consisting both of hydrogenotrophic (Methanobacterium, Methanocellales) and potential acetoclastic (Methanosarcina) members and their activity. While peat bog development was not reflected in significant changes of mcrA copy numbers, potential methane production and rates of methane release decreased. This was primarily linked to a decline of potential acetoclastic in favour of hydrogenotrophic methanogens. Although palsa peatland succession offers similarities with typical transitions from fen to bog ecosystems, the observed dynamics in methane fluxes and methanogenic communities are primarily attributed to changes within the dominant Bryophyta and Cyperaceae taxa rather than to changes in peat moss and sedge coverage, pH and nutrient regime. Overall, the palsa peatland methanogenic community was characterized by a few dominant operational taxonomic units (OTUs). These OTUs seem to be indicative for methanogenic species that thrive in terrestrial organic rich environments. In summary, our study shows that after an initial stage of high methane emissions following permafrost thaw, methane fluxes and methanogenic communities establish that are typical for northern peat bogs.